Evaluation of fructus viticis methanolic crude extract as antioxidant and anti-inflammatory in carrageenan induced acute paw oedema - Azizul, Nurul Husna (2020)
Inflammation is a natural defense mechanism against various harmful stimuli that results in pain sensation. The aim of this study was to evaluate the fruits of Vitex rotundifolia known as Fructus Viticis methanolic crude extract as antioxidant and anti-inflammatory agents in carrageenan-induced acute paw oedema. Fructus viticis has been used as a traditional medicine for the treatment of inflammation. This acute (24 hour) inflammation study involved 30 male Sprague Dawley rats (8-12 weeks and 220-280 g). Rats were equally divided into 5 groups: A (Vehicle-DMSO + Saline); B (Vehicle-DMSO + 2% λ-Carrageenan); C (Extract + Saline); D (Extract + 2% λ-Carrageenan); E (LNMMA + 2% λ-Carrageenan). Vehicle (DMSO) and extract were injected by sub plantar injection 30 minutes prior to induction of inflammatory and acute pain using 100uL of 2 % λ-carrageenan or saline into the right hind paw. The paw oedema was determined by using a digital vernier caliper, pain behaviour was assessed using Randall-Selitto test and the systolic blood pressure was taken using the tail cuff method at different time intervals (0.5, 2, 4. 6, 8, 12 and 24 hours). At the end of study, all animals were euthanized and blood sample were collected via direct cardiac puncture for full blood count analyses.. Methanolic extract of the Fructus viticis exhibits anti-inflammatory effects by delaying the development of carrageenan-induced paw oedema at 4 h to 6 h which subsequently produces analgesic effect at certain period. Moreover, the ability of Fructus viticis extract to reduce the paw oedema as well as pain is suggested to be associated with the potential of the extract reduce the infiltration of inflammatory cells which specifically the monocytes/macrophages into the hind paw. Furthermore, anti-inflammatory and analgesic effects of Fructus viticis extract might be the direct consequences of antioxidant activity of Fructus viticis. Overall, the fruit of V.rotundifolia have a potential to be developed into a novel anti-inflammatory and analgesic drugs in pharmacological field in future.